Low-cost spectral tunable microfibre knot resonator - Lim, Kok Sing; Harun, Sulaiman Wadi; Damanhuri, Siti Sarah Ahmad; Jasim, Ali Abdulhadi; Ku, H.H.; Ahmad, Harith (Institution of Engineering and Technology (IET), 2011)
A low-cost microfibre knot resonator (MKR) is fabricated and the resonant wavelength tunability characteristic of this device is investigated and demonstrated. The spacing of the transmission comb spectrum is unchanged with the temperature, but the resonant wavelength linearly shifts with the temperature change at a slope coefficient of 50.6 pm/°C. The resonant wavelength can also be tuned by applying electric current to the copper wire, which is fastened by the microfibre knot. This is attributed to the thermally induced optical phase shift in the MKR caused by the heat produced by the flow of the electric current over a short transit length. The authors' analysis indicates that the wavelength shift is linearly proportional to square of the current and the maximum tuning slope achieved is 51.3 pm/A2.